Framing "I can't draw": The influence of cultural frames on the development of drawing. (March 2014) - Cohn, Neil
Why is it that many people feel that they "can't draw"? In a recent articleCohn, 2012, I put forth a new theory that compared the cognitive structure of drawing to the cognitive structure of language. Like language, drawing uses schemas that combine in innumerable novel ways, and thus children learning to draw must acquire these schemas from the drawings in their environment. However, while most people in the United States and Europe "can't draw, " Japanese children have far greater proficiency in drawing. This paper explores reasons for this cultural disparity in graphic fluency originating in the structure of the drawing systems in those respective cultures and the beliefs that frame ideas about drawing and art education. In particular, I explore the intriguing possibility that cultural assumptions admonishing imitation of other people's drawings prohibits the acquisition of graphic schemas, thereby leading to people feeling that they "can't draw."